A study on monitoring schedules for suspended particulates in Metro Manila - Jove, Nolasco R.
Air quality monitoring has fast become an important activity of air pollution control agencies. This is essential for almost all measures taken to prevent, control or abate air pollution, from the initial assessment of existing conditions to the development of new control measures. Monitoring schedule is one of the basic considerations in air quality monitoring design. While continuous monitoring can gather data for attaining a multitude of different monitoring objectives, intermittent monitoring which involves lesser operation and maintenance costs can be used to obtain data for attaining objectives that do not strictly require continuous data gathering. However, since the latter monitoring method is subject to error, it should be so designed as to give reliable and precise data. This study is concerned with intermittent monitoring schedules for suspended particulates in Metro Manila utilizing data from two air monitoring stations. Monitoring schedules were studied to develop schedules of various sampling frequencies or intervals and periods of time with estimates of their precision in terms of confidence intervals at various confidence levels within which the true geometric mean of the particulate concentrations would lie. The study proceeded with the verification off the log normality of the concentrations of suspended particulates in Metro Manila. Findings show that, based on the plots of cumulative frequency distributions of the particulate level on a logarithmic frequency distributions of the particulate levels on a logarithmic probability paper, the concentrations generally appear to be log-normally distributed. The equations developed by HUNT (4), which are based on the assumption that the distribution of suspended particulate concentrations is log normal, was then applied to the data.